Internal control in public administration: Study in a federal public Higher Education Institution (HEI) - Soares, Larissa Fidélis; Pinho, Ruth Carvalho de Santana (Contextus - Revista Contemporânea de Economia e Gestão, 2022)
The study aimed to analyze aspects of the internal control system of the Pro-Rectory of Planning and Administration of the Federal University of Ceará (PROPLAD) from the perspective of the components of the COSO model. The research is characterized as descriptive, survey single entity, with a qualitative and quantitative approach to the data. The general analysis of internal controls shows that PROPLAD's internal control system is 58.33% similar to COSO 2013, according to the respondents. It is concluded that PROPLAD's internal controls are partially in line with the components of the COSO 2013 model and that the respondents' perception becomes more acute due to the exercise of a management position or gratified function.